Data Mining and Phylogenetic Analysis of NifH Protein of Azospirillum strain among Nitrogen-fixing Bacteria using Bioinformatics Tools - Sindhu, Saurabh; Sindhu, Divya; Yadav, SK (International Journal of Computer Sciences and Engineering, 2021)
Development of prediction tools for computational identification of nitrogen fixation (nif) genes and categorization of potential diazotrophs using high throughput sequence data has accelerated the research in the area of biological nitrogen fixation. The computational tools are recently being used for the annotation and phylogenetic analysis of nifH gene or NifH protein sequences in nitrogen-fixing bacteria. In this study, phylogenetic analysis of NifH protein using Maximum Likelihood method showed that amino acid sequences of Azospirillum brasilense showed more relatedness to Rhodospirillum rubrum and Rhodobacter capsulatus. Further, the amino acid sequences also showed similarity to nodule-forming bacteria Rhizobium etli, Rhizobium leguminosarum bv. trifolii and Sinorhizobium meliloti. Azospirillum brasilense was placed on the same clade along with Rhodopseudomonas palustris, Methylobacterium nodulans, Gluconoacetobacter diazotrophicus and Zymomonas mobilis based on NifH aminoacid sequences. On another branch, NifH amino acid sequences of Azospirillum brasilense showed relatedness to Bradyrhizobium diazoefficiens, Azorhizobium claudinodans and Acidothiobacillus ferrooxidans. However, amino acid sequences of free-living nitrogen- fixing bacteria Klebsiella pneumoniae, Azotobacter vinelanii and Azotobacter chroococcum were also placed separately on other branch. Interestingly, sequences of anaerobic bacteria Clostridium pasteurianum, Desulfatomaculum reducens and Chlorobium limicola were placed far apart. Besides this, NifH amino acid sequences of Azospirillum brasilense showed quite divergence from the sequences observed in Paenibacillus durus and Roseiflexus castenholzii. Thus, NifH amino acid sequences classified various nitrogen-fixing bacteria into different phylogenetic clusters.